Mycobacterium cosmeticum as an unusual cause of ascites. (23rd November 2010) - Addley, Jenny; McKeagney, Paul; Turner, Graham; Kelly, Martin
Abstract : Despite an increase in the prevalence of non-tuberculous mycobacterium (NTM), the diagnosis remains difficult and its treatment controversial. Prolonged duration of treatment is frequently needed and eradication is often unlikely.